2001
DOI: 10.1074/jbc.m008768200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Aldolase and Vacuolar H+-ATPase

Abstract: Vacuolar H؉ -ATPases (V-ATPases) are essential for acidification of intracellular compartments and for proton secretion from the plasma membrane in kidney epithelial cells and osteoclasts. The cellular proteins that regulate V-ATPases remain largely unknown. A screen for proteins that bind the V-ATPase E subunit using the yeast two-hybrid assay identified the cDNA clone coded for aldolase, an enzyme of the glycolytic pathway. The interaction between E subunit and aldolase was confirmed in vitro by precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(98 citation statements)
references
References 48 publications
3
94
1
Order By: Relevance
“…However, recent cross-linking experiments have suggested that the Esubunit occupies a peripheral position (58). Such an exposed position agrees with several regulatory protein-protein interactions described for the E-subunit (59,60). Accordingly, the central stalk is probably formed by the D-subunit, which is essential for coupling proton transport and ATP hydrolysis (61), and the F-subunit, which is in close proximity to the 2 The atomic coordinates of the A1C12 subcomplex of D-subunit (62,63).…”
Section: Discussionsupporting
confidence: 61%
“…However, recent cross-linking experiments have suggested that the Esubunit occupies a peripheral position (58). Such an exposed position agrees with several regulatory protein-protein interactions described for the E-subunit (59,60). Accordingly, the central stalk is probably formed by the D-subunit, which is essential for coupling proton transport and ATP hydrolysis (61), and the F-subunit, which is in close proximity to the 2 The atomic coordinates of the A1C12 subcomplex of D-subunit (62,63).…”
Section: Discussionsupporting
confidence: 61%
“…Processing of the positive clones was performed as described (13). The selected two-hybrid colonies were grown overnight in yeast/peptone/dextrose medium to stationary phase in polypropylene tubes.…”
Section: Methodsmentioning
confidence: 99%
“…The glycolytic enzyme aldolase interacts in vitro and in vivo with the E subunit of V-ATPase (13). Upon immunofluorescent staining, aldolase co-localizes extensively with V-ATPase both in the kidney proximal tubule and in the osteoclast (13).…”
Section: Expression Of the Amino-terminal Domain Of The E Subunit Resmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal cells studies have paid special attention to the spatial organization of glycolysis, because the physical concentrations of glycolytic enzymes may be associated with sites with high demand for ATP (Lu et al, 2001;Giegé et al, 2003) or other intermediates of glycolysis (Giegé et al, 2003;Fernie et al, 2004). A study in Arabidopsis established that the enzymes HXK, GADPH, and phosphofructokinase (PFK) were functionally associated with mitochondria (Giegé et al, 2003).…”
Section: Glycolysis In Plantsmentioning
confidence: 99%